Bradykinin Stimulates Renal Na+ and K+ Excretion by Inhibiting the K+ Channel (Kir4.1) in the Distal Convoluted Tubule. Issue 2 (August 2018) - Zhang, Dan-Dan; Gao, Zhong-Xiuzi; Vio, Carlos P.; Xiao, Yu; Wu, Peng; Zhang, Hao; Guo, Xi-Wen; Meng, Xin-Xin; Gu, Li; Wang, Jun-Lin; Duan, Xin-Peng; Lin, Dao-Hong; et al.
Abstract : Stimulation of BK2R (bradykinin [BK] B2 receptor) has been shown to increase renal Na + excretion. The aim of the present study is to explore the role of BK2R in regulating Kir4.1 and NCC (NaCl cotransporter) in the distal convoluted tubule (DCT). Immunohistochemical studies demonstrated that BK2R was highly expressed in both apical and lateral membrane of Kir4.1-positive tubules, such as DCT. Patch-clamp experiments demonstrated that BK inhibited the basolateral 40-pS K + channel (a Kir4.1/5.1 heterotetramer) in the DCT, and this effect was blocked by BK2R antagonist but not by BK1R (BK B1 receptor) antagonist. Whole-cell recordings also demonstrated that BK decreased the basolateral K + conductance of the DCT and depolarized the membrane. Renal clearance experiments showed that BK increased urinary Na + and K + excretion. However, the BK-induced natriuretic effect was completely abolished in KS-Kir4.1 KO (kidney-specific conditional Kir4.1 knockout) mice, suggesting that Kir4.1 activity is required for BK-induced natriuresis. The continuous infusion of BK with osmotic pump for 3 days decreased the basolateral K + conductance and the negativity of the DCT membrane. Western blot showed that infusion of BK decreased the expression of total NCC and phosphorylated NCC. Renal clearance experiments demonstrated that thiazide-induced natriuresis was blunted in the mice receiving BK infusion, suggesting that BK inhibited NCC function. Consequently, mice receiving BK infusion for 3 days were hypokalemic. We conclude that stimulation of BK2R inhibits NCC activity, increases urinary K + excretion, and causes mice hypokalemia and that Kir4.1 is required for BK2R-mediated stimulation of urinary Na + and K + excretion. Abstract : Supplemental Digital Content is available in the text.